Título Padrão: Characterization of the fishing fleet of Itaipava, ES, Brazil - Santander Neto, Jones; da Cunha Andrade, Higor Julian; Muniz, Bruno Vieira; Marvila , Nansson de Freitas; Musiello-Fernandes, Joelson (Arquivos de Ciências do Mar, 2022)
To fill the gaps of knowledge about the vessels characteristics of Espírito Santo, the present work aimed to characterize the fishing fleet on the south coast of Espírito Santo, with emphasis on the municipality of Itapemirim, in the district of Itaipava. From the collected data were recorded 331 vessels. Among the fishing gears, the longline had the highest participation in the fishing vessels of Itaipava, followed by the line and the gillnet. There was a higher incidence of vessels with a length of 12 to 14 meters, gross tonnage from 0 to 5, motorized propulsion, number of crew from 12 to 16, and manufacturing period between 2000 and 2005. Considering the variables analyzed in this study, we can observe that the Itaipava fleet is quite diversified, which has changed from essentially small to a larger fleet after focusing the construction of larger vessels between 1995 and 2005 for tuna and tuna-like fishing. With this, the evaluated fishing fleet has a large participation in the fishing economy of Espírito Santo due to its relative high load capacity and fishing resources of high economic value. Keywords: fishing vessels, fishing gear, fishing, Itapemirim